On some Algrebraic Structures of AG*-groupoids: Punyapat Kammoo, Chaiwat Namnak - Team, Support (Thai Journal of Mathematics, 2020)
An AG*-groupoid is an AG-groupoid S satisfying the identity (ab)c = b(ac) for all a, b, c ∈ S. In this paper, we study some properties of AG*-groupoids. Moreover, we construct a congruence relation on a cancellative AG*-groupoid.